Best Photo Selection - Alves, André Pires (2015)
The rising of digital photography underlies a clear change on the paradigm of the photography management process by amateur photographers. Nowadays, taking one more photo comes for free, thus it is usual for amateurs to take several photos of the same subject hoping that one of them will match the quality standards of the photographer, namely in terms of illumination, focus and framing. Assuming that the framing issue is easily solved by cropping the photo, there is still the need to select which of the well framed photos, technically similar in terms of illumination and focus, are going to be kept (and in opposition which photos are going to be discarded). The process of visual observation, on a computer screen, in order to select the best photo is inaccurate and thus becomes a generator of insecurity feelings that may lead to no discarding of photos at all. In this work, we propose to address the issue of how to help the amateur photographer to select the best photo from a set of similar photos by analysing them in technical terms. The result is a novel workflow supported by a software package, guided by user input, which will allow the sorting of the similar photos accordingly to their technical characteristics (illumination and focus) and the user requirements. As a result, we expect that the process of choosing the best photo, and discarding of the remaining, becomes reliable and more comfortable.